The Results Presentation of The Test Plants As A Natural Indicator of The Test Compounds of The Acid-Base Balance In the Teaching Materials of The Atlas to Train Scientific Reasoning Students - Raddina Aprilia Putri; Endang Susantini; Titik Taufikurohmah (IJORER : International Journal of Recent Educational Research, 2021)
The type of research applied in this research is Research and Development. The development model used is Dick and Carrey. The purpose of this research and development is to design an Atlas and apply it to train the students' scientific reasoning abilities. Atlas is a teaching materials developed and applied to high school / vocational / MA level students. The sample chosen for the implementation of the Atlas of teaching materials was grade X of VOCATIONAL Health Yannas Husada Bangkalan students. The application of plants as natural indicators of acid-base tests is the material presented in the developed Atlas. Plants selected as indicators are tested first to be presented in the Atlas. Atlas is a teaching material that can convey information related to the use of natural indicators of the acid-base test to train the students' scientific reasoning skills. The four indicators of scientific reasoning that are trained are Theoretical Reasoning, Proportional Reasoning, Probabilistic Reasoning, and Correlational Reasoning. The data shows the students' scientific reasoning ability on the post-test results, as many as 20% of students are on the high criteria, 60% are moderate criteria, and 20% are still on the low criteria from the post-test results. The post-test result data is quite increased when compared to the pretet results, which 100% of students are in the low criteria.